Legality of Secession under International Law - Abdulkareem Fendi , Pasar; Mat Basir, Salawati (International Journal of Psychosocial Rehabilitation, 2020)
This paper discussed the related question of secession as an external manifestation of the right of self-determination. The task of the present paper is to critically analyze the legality of secession and its consequences under international law and the indecisive state of international law on the legality of secession. If international law contains no explicit prohibition on unilateral secession, then on what legal basis could an act of secession be adjudged to be lawful or unlawful? Even if secession is a legally neutral act, could its consequences be regulated internationally? Put differently, on what legal criteria have certain acts of unilateral secession been subsequently legalized or opposed?